Development of LKPD Based on Socioscientific Issues (BAJA ISI) For Elementary School Students - Fidyastuti, Nita; Desstya, Anatri (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2024)
Purpose: Describe the application of Socioscientific Issue-based LKPD for students in elementary school. 2) Describe the specifications for the development of Socioscientific Issue-based Learner Worksheets (LKPD) for elementary school students. 3) Testing the validity of the Socioscientific Issue-based Learner Worksheet (LKPD) for elementary school students. Methodology: This research is a research and development that uses the Borg and Gall development mod-el, with stages including potential and problems, information gathering, product design, design validation, design revision, product trials and product revision. Results: The results show that LKPD is effective for improving science literacy and learning skills of students, as well as creating an active and enthusiastic learning atmosphere. Applications/Originality/Value: This LKPD can be used as a learning resource in the learning process to perform certain tasks that can encourage and support students in carrying out the learning process to achieve the desired understanding, skills, or attitudes.